P100 The Clinical COPD Questionnaire: Response to Pulmonary Rehabilitation. (19th November 2012) - Dilaver, D; Peasey, MM; Clark, AL; Ng, MGS; Mittal, M; Kon, SSC; Canavan, JL; Jones, SE; Polkey, MI; Man, WDC
Abstract : Background: The Clinical COPD Questionnaire (CCQ) is a 10-item health status instrument which has been shown to be reliable and valid in COPD. It takes only two minutes to complete and is simple to score, ranging from 0 (best) – 6 (worst health status). A change in the total CCQ score of 0.4 or more is considered clinically significant (Kocks et al Respir Res 2006) . There is a relative paucity of data assessing the responsiveness of the CCQ to pulmonary rehabilitation (PR). We hypothesised that the CCQ would be responsive to PR and that changes would correlate with changes in other well established health status instruments (Chronic Respiratory Questionnaire: CRQ, St George's Respiratory Questionnaire: SGRQ and the COPD Assessment Test: CAT). Methods: 75 consecutive COPD patients referred to an 8-week outpatient PR programme were recruited. The CCQ, along with the CRQ, SGRQ, CAT, and incremental shuttle walk (ISW), were measured before and after PR. Paired t-test was used to compare outcomes before and after PR, whilst Spearman's rank correlation was used to assess association between change in CCQ with change in other health status questionnaires. Results: 53 patients completed PR. Baseline characteristics were 33 Male:20 Female, mean (standard deviation) age 68.5(9.9) years, FEV1% predicted 58 (27) and ISW 224 (178) metres. There was a significant reduction (improvement) in CCQ following PR (Pre: 2.9 (1.3) versus Post: 2.1 (1.2); 95% confidence interval –0.4 to –1.0). Significant improvements were also seen in ISW, CRQ domains, SGRQ and CAT with PR. Changes in CCQ correlated significantly with changes in the other health status instruments (see table 1 ). Conclusion: The CCQ is responsive to PR and a practical alternative to longer-established health status instruments.